Understanding poor oral health among older adults in Türkiye: socioeconomic and healthcare access challenges - Irem Sevik; Aslı Davas (BMC Oral Health)
Abstract Background Oral health is an integral part of overall well-being, and older individuals are particularly vulnerable due to age-related changes and barriers to healthcare access. Despite Türkiye’s comprehensive public health insurance system, significant disparities in oral health persist, highlighting the need for targeted research and interventions. This study assesses the oral health of people aged 65 and older in Türkiye and explores the factors linked to poor oral health, such as individual characteristics, lifestyle, socioeconomic status, social support, overall health, and access to healthcare services. Methods A secondary analysis was performed using the cross-sectional 2022 Türkiye Health Survey, which gathered data from 3,144 individuals aged 65 and above. Oral health was self-reported, with poor oral health defined as participants rating their dental and gum condition as ‘bad’ or ‘very bad.’ Factors assessed included age, gender, education, social support, healthcare access, and the presence of chronic diseases. Results Among the participants, 25.8% reported poor oral health. Key factors associated with this included being older, female, having lower levels of education, difficulty communicating in one’s mother tongue, experiencing limitations in daily activities, and facing cost-related barriers to dental care. Multivariable analysis found that cost related barriers and limitations in daily activities had the strongest impact on oral health. The study also highlighted the importance of social support in maintaining better oral health. Conclusions Poor oral health in older adults in Türkiye is strongly influenced by cost-related barriers, limitations in daily activities, and lack of social support. Expanding public dental services, reducing out-of-pocket costs, and integrating oral health into chronic disease programs are critical steps. Providing culturally sensitive and mobile care options can also address mobility challenges and enhance oral health outcomes for the elderly.